Eliminating Digital Footprints - An in-depth analysis of the Case C-131/12 Google Spain v. AEDP - Chung,Kenny (2017)
The aim of this thesis has been to analyze the case of Google Spain v. AEDP, and the legal impacts of that particular case. One of the most important outcomes of the case was the establishment of the principle of the right to be forgotten. The definition of the principle of the right to be forgotten is to grant a data subject the right to have his or her personal information deleted and thus, making it inaccessible to a third-party. For a long time, there was a widespread uncertainty about the possibility of this. Because while you enable the protection of integrity for the data subject and protection of his or her personal data by removing content on the internet, you undoubtedly restrict a third-party from imparting information and the public to receive information. The core of the conflict is the clash between two fundamental rights in the Charter; namely the right to private life and protection of personal data versus the right to freedom of expression and information. This conflict was seen in the case of Google Spain v. AEDP, where the Spanish citizen Mario Gonzalez requested Google to delist a news publication about him from their search engines. The Court ruled against Google and stated that there indeed existed a right to have your personal information deleted if certain requirements were fulfilled. In addition, the Court emphasized that the full and complete protection of the Data Protection Directive meant that there should be a broad interpretation of the territorial scope as well as the material definitions in the Directive. However, as the thesis concludes, many of the questions were answered rather insufficiently. Thus, leaving us with inconclusive arguments and unresolved conflicts. The thesis delves into these gray zones as well as circumstances that are entirely exempted from the principle. Lastly, the thesis analyzes what impact the principle might have within the legal framework of the coming General Data Protection Regulation. The conclusion is that the provision containing the principle will further strengthen and reinforce the rights of the data subjects while at the same time consolidating the right to freedom of expression.
Keywords: EU law; GDPR; Data protection; Google; EU; Data Protection Directive; General Data Protection Regulation; data privacy; freedom of expression